Analysis of market & business strategies of key players in UK professional services sector For Tata Consultancy Services MBA 2012 - Pinto, Ajay Don; Sridhar, Geetha (2012)
This project is part of the Nottingham University Business School Management Project and TCS’s Global Internship Program which provides an opportunity to work on challenging projects on information technology. The key areas include: improving operational efficiency and productivity; promoting business agility; simplification and transformation; managing enterprise risk and compliance; and enabling the understanding of markets and customers. The project from Tata Consultancy Services (TCS) is to analyze six companies for their High Tech services vertical in the context of the UK / Europe market; generate a business intelligence report identifying areas in the companies analyzed, where TCS with its consulting and IT expertise could provide services. The emerging service-dominant logic to marketing is based on the resource based view of the firm; the literature review is an attempt to understand the process of relationship building in professional business-to-business services. The report will look at companies from the core competency of the firm as proposed by Barney (1991) and support this with a review of literature on the service-dominant logic to marketing and relationship marketing. The companies analyzed were KPMG Europe LLP; G4S plc; Rentokil Initial plc; Panasonic Europe Limited; Cisco International Limited and Bunge London Limited. An industry analysis was carried out for each of the companies using the Porters Five Forces and Pestle frameworks. This was supported with a review of the strategy and a core competency view of the companies to identify areas where TCS could make value addition proposals. The report has discussion for the first three companies i.e. KPMG Europe LLP, G4S plc and Rentokil Initial plc. A full detailed report for each of these companies is included in annexures 2 to 7.